An immigrant bishop : John England's adaptation of Irish Catholicism to American Republicanism - Carey, Patrick W., 1940- (The Catholic University of America Press, 2022)
"Clearly presented study of the first bishop of Charleston, South Carolina (John England). England became foremost Catholic apologist for Catholic participation and acceptance in the republic's public conversation and life...integrating faith and democratic culture"--